2010
DOI: 10.1007/s11270-010-0673-9
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Mass Balance and Internal Load in an Impacted Subtropical Isolated Wetland

Abstract: Internal loading is a critical component of the phosphorus (P) budget of aquatic systems that can control trophic conditions. While diffusion across the soil-water interface is generally considered the dominant process controlling P load to the water column, advection due to water table fluctuations can also be significant. Our objective was to evaluate the role of diffusive and advective fluxes in relation to the total P (TP) loads entering and exiting an impacted wetland in the Lake Okeechobee drainage basin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…Fick's law is based on the principle that concentration gradients trigger the exchange between two interfaces. Diffusive flux of SRP (soluble reactive phosphorus) between water and sediment was calculated according to Fick's first law of diffusion (Bhadha et al 2011;Graca et al 2006)…”
Section: Flux Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fick's law is based on the principle that concentration gradients trigger the exchange between two interfaces. Diffusive flux of SRP (soluble reactive phosphorus) between water and sediment was calculated according to Fick's first law of diffusion (Bhadha et al 2011;Graca et al 2006)…”
Section: Flux Calculationsmentioning
confidence: 99%
“…Various methods can be used to assess internal P loading, such as in situ flux measurements, sediment core incubations, mass balance methods, regression equation related to sediment P content (Nürnberg 1988), and the methods based on Fick's law, most of which were widely adopted in the previous studies (Lavery et al 2001;Bhadha et al 2011;Koriyama et al 2013). In situ flux chambers result in minimal disturbance to the sediment and overlying water (Burger et al 2007), and to some extent, is the optimal way to get realworld results about the internal flux; However, it is also the most costly way to assess internal loading from sediment.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of P concentration gradients internal to GIWs, they could serve as P sources, rather than sinks, depending on soil characteristics, hydroperiod and P concentration in inflowing waters, amongst other variables (Hoffmann et al 2009). For instance, Bhadha et al (2011) reported that internal loading (i.e., P in the soils within the GIW) accounted for 18 % of the P ''entering'' two studied historically isolated wetlands in southern Florida; a shallow ditch draining these wetlands, which eventually connected to Lake Okeechobee, accounted for 49 % of the P outflow, thus creating a potential P source. Bhadha et al (2011) also found infiltration to the ground accounted for 14 % of the P loss from the GIW, suggesting that near-surface flow gradients are important to landscape-level P dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Bhadha et al (2011) reported that internal loading (i.e., P in the soils within the GIW) accounted for 18 % of the P ''entering'' two studied historically isolated wetlands in southern Florida; a shallow ditch draining these wetlands, which eventually connected to Lake Okeechobee, accounted for 49 % of the P outflow, thus creating a potential P source. Bhadha et al (2011) also found infiltration to the ground accounted for 14 % of the P loss from the GIW, suggesting that near-surface flow gradients are important to landscape-level P dynamics. P retention is a dynamic process, and these processes can be characterized through the calculation of multiple metrics, including the equilibrium P concentration (EPC 0 ), P buffering capacity (PBC), and the maximum P sorption capacity (S max ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation